Medical relics related to Li Shizhen collected in Shanghai Museum Of Traditional Chinese Medicine - Hong Qin; Jun Han; Jin Quan (Wolters Kluwer Health/LWW, 2018)
This article introduces various editions of Ben Cao Gang Mu (《本草纲目》Compendium of Materia Medica) and displays or collects in the Shanghai Museum of Traditional Chinese Medicine (TCM), along with many other works on the study of Li Shizhen. Li Shizhen is not only a distinguished physician and pharmacist in the Ming dynasty of China but also a great scientist in human history. The most prominent contribution Li had made was sorting and developing the traditional Chinese herbal medicine, with the compilation of Ben Cao Gang Mu (《本草纲目》Compendium of Materia Medica), which represented the highest level of pharmaceutical development of TCM from a new starting line.